2012
DOI: 10.5402/2012/619251
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivatable Fluorophores

Abstract: Photoactivatable fluorophores switch from a nonemissive to an emissive state upon illumination at an activating wavelength and then emit after irradiation at an exciting wavelength. The interplay of such activation and excitation events can be exploited to switch fluorescence on in a defined region of space at a given interval of time. In turn, the spatiotemporal control of fluorescence translates into the opportunity to implement imaging and spectroscopic schemes that are not possible with conventional fluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 158 publications
(258 reference statements)
1
53
0
3
Order By: Relevance
“…Additionally, modest illumination intensities for short times are generally sufficient for activation and the presence of molecular oxygen, or any other co‐reactant, is not necessary to switch fluorescence on. Because of these evident advantages, photoactivatable fluorophores are becoming invaluable probes to track fluid dynamics in microstructured channels, translational diffusion in soft matrices, and translocating species in biological specimens …”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Additionally, modest illumination intensities for short times are generally sufficient for activation and the presence of molecular oxygen, or any other co‐reactant, is not necessary to switch fluorescence on. Because of these evident advantages, photoactivatable fluorophores are becoming invaluable probes to track fluid dynamics in microstructured channels, translational diffusion in soft matrices, and translocating species in biological specimens …”
Section: Introductionsupporting
confidence: 60%
“…Additionally,m odesti llumination intensities for short times are generallys ufficientf or activationa nd the presence of molecular oxygen, or any other co-reactant, is not necessary to switch fluorescenceo n. Becauseo ft hese evident advantages, photoactivatable fluorophores are becoming invaluablep robes to track fluid dynamics in microstructured channels, translational diffusion in soft matrices, and translocatings pecies in biological specimens. [10][11][12][13] The potentialo fp hotoactivatable fluorophores to investigate biological processes was recognized in early studies aimed at monitoring the expression of transcription factorsi n fruit-flye mbryos. [14] These seminalr eports demonstrated that the photoinduced activation of ac aged fluorescein-dextran conjugate can be exploited to track engrailed expression in fixed and immunolabeled embryos and suggested the possible use of these photoresponsive constructs to probe cell dynamics in living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] A specific functionality (typically an aniline or a phenol) of these fluorescent organic dyes is masked by linking a blocking subunit that quenches fluorescence or inhibits, for instance, proton transfer in the excited state. [3] Irreversible unmasking (decaging) by a specific chemical or physical event elicits recovery of the fluorescence and can be used as a reporter for enzyme activity, [4] as an imaging tool, [5] or for sensing specific analytes.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12] Many photoremovable groups have been applied to the activation of fluorophores. [13,14] One reason is that it is experimentally convenient to evaluate the properties of new photoremovable groups when the released molecule becomes colored and/or fluorescent. In addition, photoactivatable fluorophores possess other New Faculty iN SwitzerlaNd CHIMIA 2016, 70, No.…”
Section: Chemical To Olsmentioning
confidence: 99%